Downregulated expression of LBH mRNA in peripheral blood mononuclear cells from patients with systemic lupus erythematosus. Issue 1 (30th June 2015) - Chang, Yan; Sheng, Yujun; Cheng, Yuyan; Lin, Yan; Zhu, Zhengwei; Wen, Leilei; Yang, Chao; Yang, Lulu; Liu, Lu; Zhou, Fusheng; Zheng, Xiaodong; Zhang, Shengquan; et al.
Abstract: We performed a gene expression study to explore whether expression levels of LBH contribute to the pathogenesis of systemic lupus erythematosus (SLE) and are associated with the genome‐wide association study‐identified SNP (rs7579944 and rs906868) and the SLE Disease Activity Index (SLEDAI). Fluorescent quantitative reverse transcription polymerase chain reaction was used to examine the expression of LBH mRNA in peripheral blood mononuclear cells (PBMC) from 62 SLE patients and 69 controls. The expression levels of LBH mRNA in patients with SLE were significantly decreased compared with those in normal controls ( P  <   0.001). No significant differences were found between LBH mRNA expression levels and SLEDAI scores, SNP rs7579944 and rs906868. This study suggests that decreased expression of LBH mRNA may be correlated with the pathogenesis of SLE.